Aménagement et gestion des eaux en France : l'échec de la politique de l'eau face aux intérêts du monde agricole - Alexandre Brun (VertigO, 2003)
The water policy in France is partially based on incentive devices. Their objective is to favor the application of the right of the water by the users. In spite of positive results in certain domains, this policy did not allow to reduce to the source the pollutions of agricultural origin. The State is in a delicate situation because the farmers refuse on one hand to pay more for the cleanup and on the other hand to modify significantly them practices to reduce pollutions.